2024
DOI: 10.11591/edulearn.v18i2.21156
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review: DOGBL in enhancing EFL students’ motivation

Ari Muhammad Syifa,
Lilla Musyahda,
David Segoh

Abstract: This systematic literature review (SLR) aimed to investigate the potential of digital online game-based learning (DOGBL) to enhance motivation in English as a foreign language (EFL). Online gaming has grown in popularity among students, opening up the possibility of using games as powerful instructional resources. Academic achievement depends on motivation, and this study, led by self-determination theory (SDT), explored how external rules, like rewards and recognition, could increase motivation in EFL utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…The effective regulation of learners' cognitive, affective and behavioural processes as they interact in the learning environment is critical to their academic success (Code, 2020). As academic success and learning effectiveness relies on motivation (Dita et al, 2020;Syifa, 2024), it was suggested that college students should stimulate their motivation for independent learning, enhance their motivation in order to learn and develop independent learning skills in learning (Lei et al, 2024).…”
Section: Background Of Studymentioning
confidence: 99%
“…The effective regulation of learners' cognitive, affective and behavioural processes as they interact in the learning environment is critical to their academic success (Code, 2020). As academic success and learning effectiveness relies on motivation (Dita et al, 2020;Syifa, 2024), it was suggested that college students should stimulate their motivation for independent learning, enhance their motivation in order to learn and develop independent learning skills in learning (Lei et al, 2024).…”
Section: Background Of Studymentioning
confidence: 99%